Optimism in a time of uncertainty. Spinoza, Kant and the eternal peace - Ingrid Roos (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This article describes ideas of Enlightenment thinkers about the building of a democratic state with responsible and rationally thinking citizens. The article starts with the ideas of Spinoza, formulated in the seventeenth century, and will end in our time, where democracy is under threat. ~ Design/Research method: The article relies on professional publications, both within the fields of philosophy and political sociology. ~ Conclusions/findings: The study concludes that the optimistic expectations about the increase of democracy and the stability of democratic institutions in the world are no longer valid. ~ Originality/Value of the article: Recent developments in the political field in the western world make this optimism questionable
Keywords: 330; Philosophy; political sociology; democracy; Philosophy; political sociology; democracy